SOCIAL ECONOMIC LAW IN THE CONTEXT OF GLOBALISATION: A LITERATURE-BASED DISCUSSION - Loso Judijanto; Al-Amin (Adisam Publisher, 2025)
Social economic law is a branch of law that regulates the interaction between economic activities and social goals to ensure equitable wealth distribution, labour protection, and community welfare within a sustainable and inclusive regulatory framework. The research method used is literature. The results show that in the face of challenges such as income inequality and resource exploitation, countries are expected to adopt balanced and adaptive regulations to achieve sustainable development. The research also emphasises the importance of cross-sector collaboration and international cooperation to create a legal framework capable of effectively addressing global issues. Through inclusive policy formulation and a holistic approach, social economic law can serve as the foundation for achieving a more equitable and sustainable distribution of wealth in the global community.